2023
DOI: 10.1038/s41467-023-37215-3
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of antibody-specific deglycosylation and immune evasion by Streptococcal IgG-specific endoglycosidases

Abstract: Bacterial pathogens have evolved intricate mechanisms to evade the human immune system, including the production of immunomodulatory enzymes. Streptococcus pyogenes serotypes secrete two multi-modular endo-β-N-acetylglucosaminidases, EndoS and EndoS2, that specifically deglycosylate the conserved N-glycan at Asn297 on IgG Fc, disabling antibody-mediated effector functions. Amongst thousands of known carbohydrate-active enzymes, EndoS and EndoS2 represent just a handful of enzymes that are specific to the prote… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 100 publications
0
7
1
Order By: Relevance
“…The EndoS2-IgG1 Fc crystal structure demonstrates how the enzyme contacts IgG1 Fc with its GH and CBM domains, as also elucidated from hydrogen-deuterium exchange of an EndoS2-rituximab complex ( 51 ) and similarly observed for the related EndoS complex ( 55 , 56 ). However, upon binding to the Fc, EndoS2 undergoes a domain rearrangement, with the relative orientation of GH, LRR, and hIg domains changing ( Figs.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The EndoS2-IgG1 Fc crystal structure demonstrates how the enzyme contacts IgG1 Fc with its GH and CBM domains, as also elucidated from hydrogen-deuterium exchange of an EndoS2-rituximab complex ( 51 ) and similarly observed for the related EndoS complex ( 55 , 56 ). However, upon binding to the Fc, EndoS2 undergoes a domain rearrangement, with the relative orientation of GH, LRR, and hIg domains changing ( Figs.…”
Section: Discussionmentioning
confidence: 64%
“…EndoS and EndoS2 are multi-domain enzymes, comprised of a catalytic glycosyl hydrolase (GH) domain, a leucine-rich repeat (LRR) domain, a hybrid immunoglobulin fold (hIg) domain, and the so-called carbohydrate-binding module (CBM) ( 50 , 52 , 53 , 54 ); EndoS additionally has N- and C-terminal 3-helix bundles ( 50 , 53 ). Recent structural studies revealed that the functional role of the CBM in EndoS was not to bind carbohydrates but rather to specify peptide binding to the Fc surface ( 55 , 56 ). The structural basis for IgG recognition by EndoS2 is less clear, although hydrogen-deuterium exchange data show a role for both GH and CBM domains in Fc binding ( 51 ), which indicates a similar mode of Fc recognition to that observed for EndoS ( 55 , 56 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Rituximab, an anti-CD20 chimeric monoclonal antibody, targets B cells and is often used as a therapeutic for B cell lymphomas ( 37 ). After purification by protein A affinity chromatography ( 38 ) and treatment with the IgG-specific endoglycosidase EndoS2 ( 39 , 40 ) to remove heterogeneous glycosylation at residue Asn297, three potential products with unique masses that are easily detectable by liquid chromatography–mass spectrometry (LC-MS) can result from such a coexpression, including an intact Fc (~50 kDa), an intact IgG (~150 kDa), and a monovalent IgG molecule (Fab 1 Fc; ~100 kDa) ( Fig. 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…The bound G2S2-oxazoline is carried by EndoSz-D234M to the target, Asn-GlcNAc (+1). How EndoSz-D234M targets Asn-GlcNAc (+1) remains unknown, which is presumably mediated by the β-sandwich domain as which EndoS had identified interactions with the CH2-CH3 joint of Fc . According to the structural analysis of the EndoSz-D234M/G2S2-oxazoline complex (Figure b), Gln304 and Asp280 might play important roles in accommodating NAG (+1), especially for the acetamido group.…”
Section: Resultsmentioning
confidence: 99%